MARENGGE-RENGGE; UPAYA MEMBANTU KEBUTUHAN KELURGA (Studi Terhadap Perempuan di Pasar Sangkumpal Bonang Kota Padangsidimpuan) - Puji Kurniawan (Institut agama islam negeri Padangsidimpuan, 2020)
Batak women are very instrumental in helping to improve the family economy by selling small to weeks (parrengge-rengge.) This is due to the low income of the husband, the high level of necessities of life and the cost of children's education and the drive to obtain a more established life. The lack of education coupled with the lack of life skills makes Batak women help families with marreng-gengge. This paper reviews the lives of parrengge-rengge women in helping families.